Kupyaphores are zinc homeostatic metallophores required for colonization of Mycobacterium tuberculosis - Mehdiratta, Kritee; Singh, Shubham; Sharma, Sachin; Bhosale, Rashmi S.; Choudhury, Rahul; Masal, Dattatraya P.; Manocha, Alzu; Dhamale, Bhushan Dilip; Khan, Naseem; Asokachandran, Vivekanand; Sharma, Pooja; Ikeh, Melanie; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2022)
Mycobacterium tuberculosis (Mtb) endures a combination of metal scarcity and toxicity throughout the human infection cycle, contributing to complex clinical manifestations. Pathogens counteract this paradoxical dysmetallostasis by producing specialized metal trafficking systems. Capture of extracellular metal by siderophores is a widely accepted mode of iron acquisition, and Mtb iron-chelating siderophores, mycobactin, have been known since 1965. Currently, it is not known whether Mtb produces zinc scavenging molecules. Here, we characterize low-molecular-weight zinc-binding compounds secreted and imported by Mtb for zinc acquisition. These molecules, termed kupyaphores, are produced by a 10.8 kbp biosynthetic cluster and consists of a dipeptide core of ornithine and phenylalaninol, where amino groups are acylated with isonitrilecontaining fatty acyl chains. Kupyaphores are stringently regulated and support Mtb survival under both nutritional deprivation and intoxication conditions. A kupyaphore-deficient Mtb strain is unable to mobilize sufficient zinc and shows reduced fitness upon infection. We observed early induction of kupyaphores in Mtb-infected mice lungs after infection, and these metabolites disappeared after 2 wk. Furthermore, we identify an Mtb-encoded isonitrile hydratase, which can possibly mediate intracellular zinc release through covalent modification of the isonitrile group of kupyaphores. Mtb clinical strains also produce kupyaphores during early passages. Our study thus uncovers a previously unknown zinc acquisition strategy of Mtb that could modulate host-pathogen interactions and disease outcome.
Keywords: metallophore; nutritional immunity; tuberculosis; zinc

Ready access to densely substituted furans using Tsuji-Wacker type cyclization - Masal, Dattatraya P.; Choudhury, Rahul; Singh, Aman; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2022)
A competent method for the construction of highly substituted furans catalyzed by Pd(II) and Cu(II) chloride has been developed. The method provides easy access to di-, tri-, and tetrasubstituted furans from corresponding diols with relatively mild conditions in a unified strategy. The developed method has been successfully tested with more than 25 substrates, which resulted in furans of multiple substitution patterns with up to 84% isolated yields.

Enzymatic pathway for kupyaphore degradation in mycobacterium tuberculosis: mechanism of metal homeostasis and turnover - Bhosale, Rashmi S.; Chakraborty, Arnab; Wong, Tsung-Yun; Masal, Dattatraya P.; Choudhury, Rahul; Srivastava, Sonali; Reddy, D. Srinivasa; Aldrich, Courtney C.; Kamat, Siddhesh S.; Mohanty, Debasisa; Gokhale, Rajesh S. (ACS Chemical Biology, 2025)
Metallophores are essential for metal homeostasis, regulating availability, and mediating host-pathogen interactions. Kupyaphores are specialized metallophores produced by Mycobacterium tuberculosis (Mtb) that primarily chelate zinc to support bacterial survival. Elevated kupyaphore levels early in infection highlight their importance, while their rapid decline, despite increasing bacterial loads, indicates tightly regulated mechanisms of production, consumption, and degradation. However, the processes driving kupyaphore catabolism and their role in preventing zinc toxicity in Mtb remain unclear. Here, we show that covalent modification of the isonitrile moiety in kupyaphores releases zinc, triggering degradation through a sequential three-step enzymatic pathway encoded by Mtb. Isonitrile hydratase converts isonitrile groups into formamides, which are subsequently processed into amines by N-substituted formamide deformylase and ultimately oxidized to beta-ketoesters by amine oxidases. The biological significance of this pathway is underscored by the upregulation of these genes under metal-depleted and biofilm-forming conditions. Mutant Mtb strains lacking these genes exhibit impaired growth in metal-limiting environments and reduced levels of biofilm formation. Catalytic intermediates detected in Mtb cultures and infected mouse lung tissues confirm the pathway's in vivo activity. Further, genome mining reveals that similar enzymes are conserved across organisms producing isonitrile-containing metabolites, emphasizing the broader importance of this pathway. Understanding these processes could pave the way for novel therapeutic strategies targeting kupyaphore catabolism.

Gram-scale synthesis of (±)-tylophorine - Masal, Dattatraya P.; Reddy, D. Srinivasa (Synlett, 2025)
We report a practical scalable synthesis of the natural product (+/-)-tylophorine by using an operationally simple protecting-group-free route from readily accessible starting materials. Synthesis of a cyclic N-acetyl diester compound through cyclization, followed by two key steps (decarboxylation and a Clemmensen reduction), provides access to the target molecule.
Keywords: alkaloids; Clemmensen reduction; decarboxylation; gram-scale synthesis; tylophorine

Interplay between genotoxic stress and STING activation in cellular senescence and inflammatory responses - Dash, Anshurekha; Kulkarni, Akshay S.; Irshad, Faisal; Masal, Dattatraya P.; Manhas, Diksha; Nandi, Utpal; Reddy, D. Srinivasa; Goswami, Anindya (International Immunopharmacology, 2025)
STING pathway is activated by endogenous or exogenous DNA damage and is known to trigger cell-intrinsic innate immunity. In this study, we demonstrated that the Peharmaline analog NDS101781 is a potent genotoxic molecule to trigger cellular senescence via innate immune-responsive STING activation. We found NDS101781 consistently modulated the expression of DDR markers including gamma-H2AX, Rad51, PARP1, ATM and MRE11 in breast cancer cells with concomitant amplification in the hallmarks of senescence along with STING signaling mediators which is intricately involved in NDS101781-mediated senescence activation as evidenced by significant reduction in the senescent population in si-TMEM173-transfected cells. In vitro findings proclaimed that STING activation by NDS101781 is crucial for p21-mediated senescence augmentation, a process regulated by ATM and p53 via a pathway independent of cGAS. Although STING is activated by both canonical and non-canonical manner, our mechanistic findings indicated that ATM played a crucial role in early activation of NDS101781 driven STING signaling via p53 activation and stimulation of pTBK1, NF-kappa B, and p-IRF3, through a non-canonical cascade in cGAS-independent mechanism. The results also indicated that interference of canonical and non-canonical STING activation, responsible for NF-kappa B stimulation leading to IL-6 generation. Intriguingly, the inhibition of ATM diminished senescence hallmarks; however, suppression of ATM as well as p21 neutralization triggered apoptotic cascade and thus regulating the SASP factors. However, transient knockdown of p21 moderately instigated the apoptotic mediators underscoring that NDS101781 mediated senescence induction delayed programmed cell death under intact p21 conditions. Moreover, pharmacokinetics of NDS101781 confirmed its excellent half-life in a preclinical model and in vivo studies confirmed that NDS101781 significantly inhibited tumor growth in a syngeneic aggressive 4T1-p53 breast cancer model.
Keywords: ATM; IL-6; Peharmaline; Senescence; STING